Inspection of Phytochemical Content and In Vitro Antioxidant Profile of Gnaphalium luteoalbum L.: An Unexplored Phytomedicine - Md. Sahab Uddin ,; G.M. Sala Uddin ,; Mst. Marium Begum ,; Yesmin Begum ,; Oscar Herrera-Calderon ,; Md. Manjurul Islam ,; Mohamed M. Abdel-Daim, (Journal of Pharmacy and Nutrition Sciences, 2017)
Background:Oxidative stress is intensely linked with several pathological manifestations. Searching for medicinal plant with the superior safety profile for the treatment of oxidative stress related disorders are ongoing due to multiple unwanted effects associated with synthetic antioxidants. Therefore the purpose of this study was to examine the phytochemical content, in vitro antioxidant potentiality of crude methanol extract (CME), carbon tetrachloride fraction (CTF), petroleum ether fraction (PEF), chloroform fraction (CLF) and ethyl acetate fraction (EAF) of aerial parts of Gnaphalium luteoalbum (GL) L. Methods:The aerial parts of the GL were extracted with methanol followed by fractionation using carbon tetrachloride, petroleum ether, chloroform and ethyl acetate.The phytochemical screening of this plant was performed by using standard methods to evaluate the existence of alkaloids, carbohydrates, phenols, flavonoids, saponins, tannins, terpenoids and fixed oils.Antioxidant potentiality was estimated by, 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl (OH) and nitric oxide (NO) radical scavenging tests. Total antioxidant capacity (TAC), total phenolic content (TPC) and total flavonoid content (TFC) were also measured. Results: Phytochemical analysis of the aerial parts of GL confirmed the presence of carbohydrates, phenols, flavonoids and saponins in crude extract and its all fractions. The CME showed the highest scavenging activity (43.28%) with IC50 of 398.49 μg/mL in the DPPH radical scavenging test. The IC50 values of EAF, CME were statistically significant (P < 0.05, P < 0.01) with respect to ascorbic acid (ACA). For OH and NO radical scavenging tests maximum scavenging (48.39%, 69.64%) was also reported for CME compared to CTF, PEF, CLF and EAF. Compared to ACA, in case of OH and NO radical scavenging activities the IC50 values of CME were markedly significant (P < 0.01, P < 0.05). In the TAC test, CME showed the highest antioxidant activity (absorbance, 2.6 nm) related to other fractions. TPC was found to be the highest in the CME (115.96 mg of gallic acid equivalent/g of dried extract) rather than other fractions. The ranking order of CTF, PEF, CLF, EAF and CME for TFC was 48.67 < 55.75 < 65.29 < 71.35 < 82.29 mg quercetin equivalent/g of dried extract. Conclusion: The existing study suggested that CME of the aerial parts of GL can be used as a natural source of antioxidant which might be effective towards preventing or slowing oxidative stress related disorders.